АДЕКВАТНАЯ ТЕМПЕРАТУРНАЯ СТИМУЛЯЦИЯ ДЕЯТЕЛЬНОСТИ КАРДИОРЕСПИРАТОРНОЙ СИСТЕМЫ (Experimental biology, 2009)
Adequate temperature stimulation of four sensitive zones of a skin against carrying out of functional tests of Shtange and Genche has revealed possibility of application of such stimulation for functional condition correction of cardiorespiratorical systems
Keywords: cardiorespiratorical systems; adequate temperature stimulation